2021
DOI: 10.2302/kjm.2021-0003-oa
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR Screening Tests for SARS-CoV-2 with Saliva Samples in Asymptomatic People: Strategy to Maintain Social and Economic Activities while Reducing the Risk of Spreading the Virus

Abstract: The year 2020 will be remembered for the coronavirus disease 2019 (COVID-19) pandemic, which continues to affect the whole world. Early and accurate identification of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is fundamental to combat the disease. Among the current diagnostic tests, real-time reverse transcriptase-polymerase chain reaction (RT-qPCR) is the most reliable and frequently used method. Herein, we discuss the interpretation of RT-qPCR results relative to viral infectivity. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
2
17
0
2
Order By: Relevance
“…On the contrary, it was very useful to quickly and accurately detect individuals who were capable of transmitting the infection to others [22,23,25,26] Another relevant issue is the high proportion of PCR-confirmed negative cases in antigen-negative participants, and the fact that three non-confirmed cases were found in subjects with very a high Ct, above 35. Even in the case of low sensitivity, it could be assumed that false negatives, infected subjects not detected by RADT, are cases with low viral loads that are therefore limited as potential sources of infection, at least in population screening and outside enclosed places, where there is a high potential for transmission (i.e., health facilities, COVID-19 testing centers/sites, care homes, prisons or schools) [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it was very useful to quickly and accurately detect individuals who were capable of transmitting the infection to others [22,23,25,26] Another relevant issue is the high proportion of PCR-confirmed negative cases in antigen-negative participants, and the fact that three non-confirmed cases were found in subjects with very a high Ct, above 35. Even in the case of low sensitivity, it could be assumed that false negatives, infected subjects not detected by RADT, are cases with low viral loads that are therefore limited as potential sources of infection, at least in population screening and outside enclosed places, where there is a high potential for transmission (i.e., health facilities, COVID-19 testing centers/sites, care homes, prisons or schools) [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The nasopharyngeal or oropharyngeal swabs that are widely used for PCR assays can be difficult and uncomfortable to collect. Other more convenient specimen types, such as saliva 39 41 and nasal swabs, 42 are being investigated, with encouraging results. A systematic review of the diagnostic performance of different swabs found that saliva and nasal swabs had good performance and were acceptable alternatives to nasopharyngeal swabs.…”
Section: Practical Considerationsmentioning
confidence: 99%
“… 39 However, pooled results from saliva samples might still be useful for quickly identifying and isolating individuals with a high concentration of virus particles. 41 …”
Section: Practical Considerationsmentioning
confidence: 99%
“… 4–6 Many countries (eg, South Korea, Germany, and Japan) are already using routine saliva tests to control the spread of the virus while preserving social and economic activity. 7 …”
Section: Introductionmentioning
confidence: 99%